Comparison of infectious complications after spleen preservation versus splenectomy during laparoscopic distal pancreatectomy for benign or low‐grade malignant pancreatic tumors: A multicenter, propensity score‐matched analysis. (13th July 2022) - Lee, Woohyung; Hwang, Dae Wook; Han, Ho‐Seong; Han, In Woong; Heo, Jin Seok; Unno, Michiaki; Ishida, Masaharu; Tajima, Hiroshi; Nishizawa, Nobuyuki; Nakata, Kohei; Seyama, Yasuji; Isikawa, Yoshiya; et al.
Abstract: Background: Previous studies have reported contrasting results regarding the advantages of spleen preservation during laparoscopic distal pancreatectomy (LDP) for preventing infectious complications. Methods: A total of 3787 patients who underwent LDP for benign or low‐grade malignant pancreatic disease in 92 centers across Korea and Japan were included in this retrospective study. Postoperative infectious complications and other complications were compared between LDP with splenectomy (LDPS) and LDP with spleen preservation (LSPDP) by propensity score matching (PSM) analysis. Results: After PSM, the LSPDP group had a lower rate of overall infectious complications ( P  = .079) and a significantly lower rate of intra‐abdominal abscess ( P  = .014) compared with the LDPS group. Within the LSPDP group, the vessel preservation subgroup had a significantly higher rate of infectious complications ( P  = .002) compared with the vessel resection subgroup. Low‐volume centers had a higher rate of intra‐abdominal abscess than high‐volume centers in the LSPDP group ( P  = .001) and the splenic vessel preservation subgroup ( P  = .003). Conclusions: Spleen preservation in LDP for benign or borderline malignant pancreatic diseases was advantageous in lowering the risk of infectious complications, specifically intra‐abdominal abscess. However, the risk of intra‐abdominal abscess may differ according to the level of surgeon's experience. Abstract : Lee and colleagues retrospectively compared the postoperative infectious complications according to spleen preservation in laparoscopic distal pancreatectomy performed at 91 centers in Korea and Japan. Spleen preservation was significantly associated with lower rates of intraabdominal abscess, but the risk of intraabdominal abscess differed according to the surgeon's level of experience.